How Views of the Organization of Primary Care Among Patients with Hypertension Vary by Race or Ethnicity. Issue 9 (17th April 2018) - Jackson, George L; Stechuchak, Karen M; Weinberger, Morris; Bosworth, Hayden B; Coffman, Cynthia J; Kirshner, Miriam A; Edelman, David
Abstract: Introduction: We assessed potential racial or ethnic differences in the degree to which veterans with pharmaceutically treated hypertension report experiences with their primary care system that are consistent with optimal chronic illness care as suggested by Wagner's Chronic Care Model (CCM). Materials and Methods: A cross-sectional analysis of the results of the Patient Assessment of Chronic Illness Care (PACIC), which measured components of the care system suggested by the CCM and was completed at baseline by participants in a hypertension disease management clinical trial. Participants had a recent history of uncontrolled systolic blood pressure. Results: Among 377 patients, non-Hispanic African American veterans had almost twice the odds of indicating that their primary care experience is consistent with CCM features when compared with non-Hispanic White patients (odds ratio (OR) = 1.86; 95% confidence interval (CI) = 1.16–2.98). Similar statistically significant associations were observed for follow-up care (OR = 2.59; 95% CI = 1.49–4.50), patient activation (OR = 1.80; 95% CI = 1.13–2.87), goal setting (OR = 1.65; 95% CI = 1.03–2.64), and help with problem solving (OR = 1.62; 95% CI = 1.00–2.60). Conclusions: Non-Hispanic African Americans with pharmaceutically treated hypertension report that the primary care system more closely approximates the Wagner CCM than non-Hispanic White patients.